2017
DOI: 10.1038/icb.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of Gas6/Axl signal in allergic airway responses during RSV vaccine‐enhanced disease

Abstract: Respiratory syncytial virus (RSV) is a common virus that causes lower respiratory infections across a wide range of ages. A licensed RSV vaccine is not available because vaccination with formalin-inactivated RSV (FI-RSV) and the subsequent RSV infection cause not only insufficient induction of neutralizing antibodies but also severe allergic airway responses, termed FI-RSV vaccine-enhanced disease (FI-RSV VED). However, the underlying mechanism has not been identified, although a Th2-biased immune response is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The expression levels of Gas6 after infection are largely determined by the antigenic properties of individual pathogens. For RSV, G glycoprotein is reported to bind CX3CR1 (49), which initiates Gas6 production (50). Further studies are required for dissecting the mechanisms underlying infection-induced Gas6 production and immune cell polarization.…”
Section: Discussionmentioning
confidence: 99%
“…The expression levels of Gas6 after infection are largely determined by the antigenic properties of individual pathogens. For RSV, G glycoprotein is reported to bind CX3CR1 (49), which initiates Gas6 production (50). Further studies are required for dissecting the mechanisms underlying infection-induced Gas6 production and immune cell polarization.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in both T cell types, the capability of the cells to secrete IFN-γ was significantly reduced due to the absence of GAS6 in DCs. A recent study has shown that AXL signaling downregulates IL-12 production by DCs ( 20 ), a cytokine required for generation of IFN-γ producing T cells ( 21 ). In addition, the AXL/GAS6 pathway was shown to diminish IFN-γ expression in NK cells as well as the expression of its master regulator, T-BET ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some diseases and pathological processes may involve the binding of TAM to PtdSer. For example, AD [ 7 ], Tumor and cancer such as breast cancer [ 22 ], DENV [ 15 ], EBOV [ 10 12 ], and RSV [ 16 18 ] are involved.…”
Section: Immune Receptors For Ptdsermentioning
confidence: 99%
“…As Immune and blood coagulation play a vital role in the human body and within them, PtdSer is essential for the normal execution of specific immune and coagulation processes. Once the functions of PtdSer are abnormal, they will cause many diseases, including Scott syndrome [ 3 ], Systemic lupus erythematosus (SLE) [ 4 ], Essential hypertension (EH) [ 5 ], Hemophilia A [ 6 ], Alzheimer’s disease (AD) [ 7 ], Human Immunodeficiency Virus (HIV) [ 8 ], Ebola virus (EBOV) [ 9 12 ], Dengue virus (DENV) [ 13 15 ] and Respiratory Syncytial Virus (RSV) [ 16 18 ], and certain tumors or cancers [ 19 22 ]. It was also speculated that PtdSer might be a potential mechanism or participant of inflammation and coagulation abnormalities in COVID-19 [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%